2021
DOI: 10.1142/s0217595921400169
|View full text |Cite
|
Sign up to set email alerts
|

Price and Product Quality Decisions for a Two-Echelon Supply Chain in the Blockchain Era

Abstract: Frequent problems of counterfeiting have spawned consumer demands to monitor the entire supply chain. The application of blockchain technology with anti-counterfeiting and traceability can improve the reliability and authenticity of product information and eliminate consumer doubts about product quality. Furthermore, based on the transparency of blockchain technology, brand suppliers can independently obtain the market demand information through information sharing. This paper introduces a consumer suspicion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…On the hardware, the server maintains the blockchain and hash tables through memory resources. As the amount of blockchain data continues to increase, memory consumption is reduced by deleting the blocks generated earlier and only retaining the new blocks, thus ensuring timely modification of the data in the event of a fork in the blockchain [9]. At the same time, the server also needs to provide large In software, each node in the background maintains an array of IP addresses and port numbers of other nodes.…”
Section: Lucky Numbersmentioning
confidence: 99%
“…On the hardware, the server maintains the blockchain and hash tables through memory resources. As the amount of blockchain data continues to increase, memory consumption is reduced by deleting the blocks generated earlier and only retaining the new blocks, thus ensuring timely modification of the data in the event of a fork in the blockchain [9]. At the same time, the server also needs to provide large In software, each node in the background maintains an array of IP addresses and port numbers of other nodes.…”
Section: Lucky Numbersmentioning
confidence: 99%
“…Zhou et al [253] and Sun et al [254] conducted detailed analysis and proof on the cost of blockchain in twoechelon supply chain where only one supplier and one retailer exist. Zhou et al [253] pointed out that, blockchainenabled supply chains are not necessarily superior than non-blockchain ones, which is closely related to the reliability of information and the transparency cost of products.…”
Section: Cost Of Blockchain In Supply Chainmentioning
confidence: 99%
“…Zhou et al [253] and Sun et al [254] conducted detailed analysis and proof on the cost of blockchain in twoechelon supply chain where only one supplier and one retailer exist. Zhou et al [253] pointed out that, blockchainenabled supply chains are not necessarily superior than non-blockchain ones, which is closely related to the reliability of information and the transparency cost of products. Based on full equilibrium results through the Stackelberg game between the supplier and the retailer designed in the paper, the authors concluded that the retailer can tolerate higher blockchain adopting cost than supplier in most cases especially when the product cost is high, while supplier can tolerate a higher adopting cost only when both the product cost and consumers' willing to pay are low.…”
Section: Cost Of Blockchain In Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of transactions is achieved through a process called mining which ensures trust and security. Middlemen's removal will lead to reduced corruption and fair pricing of products (Sun et al 2022).…”
Section: Trading In Trust Environment Without Middlemen (Dv13)mentioning
confidence: 99%